1989
DOI: 10.1007/bf00274990
|View full text |Cite
|
Sign up to set email alerts
|

Xenografting of fetal pig ventral mesencephalon corrects motor asymmetry in the rat model of Parkinson's disease

Abstract: A suspension of cells from embryonic day 21 fetal pig ventral mesencephalon was transplanted into the striatum of 20 immunosuppressed rats with 6-hydroxydopamine-induced lesions of the nigrostriatal dopamine pathway. Of these rats, 15 showed reduction of amphetamine-induced ipsilateral rotation by 9 weeks and complete reversal of rotation by 14-17 weeks. Animals maintained stable reversal of rotations (contralateral direction) until cessation of Cyclosporin A (CyA) treatment at 15-20 weeks. Within 4-9 weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…In fact, porcine fetal cells have been proven to be an efficient source for cell therapy in animal models of neurodegenerative diseases. Interest in these cells started to grow after first studies revealed that xenografts derived from the ventral mesencephalon of pigs (21–26 days of gestation) could survive in the brain of a rat model of Parkinson disease under immunosuppression (Freeman et al, 1988; Huffaker et al, 1989). Beyond the long-term survival, xenotransplanted neural cells also displayed a long-distance axonal outgrowth (Wictorin et al, 1990; Deacon et al, 1994).…”
Section: Intracerebral Xenotransplantationmentioning
confidence: 99%
“…In fact, porcine fetal cells have been proven to be an efficient source for cell therapy in animal models of neurodegenerative diseases. Interest in these cells started to grow after first studies revealed that xenografts derived from the ventral mesencephalon of pigs (21–26 days of gestation) could survive in the brain of a rat model of Parkinson disease under immunosuppression (Freeman et al, 1988; Huffaker et al, 1989). Beyond the long-term survival, xenotransplanted neural cells also displayed a long-distance axonal outgrowth (Wictorin et al, 1990; Deacon et al, 1994).…”
Section: Intracerebral Xenotransplantationmentioning
confidence: 99%
“…To avoid the ethical issues of using human FVM tissue, studies have examined the use of porcine FVM tissue as an alternative transplant [50-59]. In contrast to the human FVM tissue, porcine tissue is relatively easy to obtain and harvest can be timed accordingly to transplant days.…”
Section: Overview Of Cell Transplantation Studies In Pd: Focus On mentioning
confidence: 99%
“…In 1989, Huffaker and colleagues demonstrated porcine neuroblasts, derived from pig foetal ventral mesencephalum at 21 days of gestation, were able to survive 15-20 weeks in a rat model of Parkinson's disease, albeit with supplements of the immunosuppressant, cyclosporine A (Huffaker et al, 1989). Immunological analysis of the transplanted tissue revealed the presence of tyrosine hydroxylase (TH) positive dopaminergic neurons in grafted striatum.…”
Section: Xenotransplantation In Parkinson's Diseasementioning
confidence: 99%